Artesunate Inhibits the Growth Behavior of Docetaxel-Resistant Prostate Cancer Cells - Vakhrusheva, Olesya; Erb, Holger H. H.; Bräunig, Vitus; Markowitsch, Sascha D.; Schupp, Patricia; Baer, Patrick C.; Slade, Kimberly Sue; Thomas, Anita; Tsaur, Igor; Puhr, Martin; Culig, Zoran; Cinatl, Jindrich; et al. (Frontiers in Oncology, 2022)
Novel therapeutic strategies are urgently needed for advanced metastatic prostate cancer (PCa). Phytochemicals used in Traditional Chinese Medicine seem to exhibit tumor suppressive properties. Therefore, the therapeutic potential of artesunate (ART) on the progressive growth of therapy-sensitive (parental) and docetaxel (DX)-resistant PCa cells was investigated. Parental and DX-resistant PCa cell lines DU145, PC3, and LNCaP were incubated with artesunate (ART) [1-100 µM]. ART-untreated and ‘non-cancerous’ cells served as controls. Cell growth, proliferation, cell cycle progression, cell death and the expression of involved proteins were evaluated. ART, dose- and time-dependently, significantly restricted cell growth and proliferation of parental and DX-resistant PCa cells, but not of ‘normal, non-cancerous’ cells. ART-induced growth and proliferation inhibition was accompanied by G0/G1 phase arrest and down-regulation of cell cycle activating proteins in all DX-resistant PCa cells and parental LNCaP. In the parental and DX-resistant PC3 and LNCaP cell lines, ART also promoted apoptotic cell death. Ferroptosis was exclusively induced by ART in parental and DX-resistant DU145 cells by increasing reactive oxygen species (ROS). The anti-cancer activity displayed by ART took effect in all three PCa cell lines, but through different mechanisms of action. Thus, in advanced PCa, ART may hold promise as a complementary treatment together with conventional therapy.